Population‐based values and abnormalities of the electrocardiogram in the general Dutch population: The LifeLines Cohort Study - van der Ende, M. Yldau (Clin Cardiol, 2017)
BACKGROUND: Our aim is to present average values and prevalence of electrocardiographic (ECG) abnormalities among the general Dutch population in the LifeLines Cohort. HYPOTHESIS: The ECG values previously studied in the Caucasian population of smaller cohorts will be confirmed with ECG data from LifeLines. METHODS: ECG data of 152 180 individuals age 18 to 93 years were available. Individuals with cardiovascular risk factors were excluded to analyze the healthy population. Average values of the ECG for the healthy population were presented as means with 95% and 99% confidence intervals and as medians with first and 99th percentiles. RESULTS: Median heart rate was highest in the youngest and oldest individuals of the healthy population. Median duration of P wave, PQ interval, and QRS duration were longer in males compared with females. In contrast, median QT interval corrected for heart rate was higher in females. In general, the above‐mentioned parameters increased with age. The prevalences of ECG abnormalities adjusted for the Dutch population were 0.9% for atrial fibrillation or flutter, 1.4% for premature atrial complexes, 0.5% for myocardial infarction, 2.1% for ventricular premature complexes, 1.0% for left ventricular hypertrophy, 8.1% for P‐R interval >200 ms, and 0.8% for bundle branch block. CONCLUSIONS: Our study provides an overview of average values and ECG abnormalities and confirms data of previous smaller studies. In addition, we evaluate the age‐ and sex‐dependent normal limits of the P wave and QRS duration and confirm in detail the frontal plane QRS‐T angle on the ECG.